(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This article explores the intersection of copyright law and artificial intelligence (AI), focusing on the challenges of determining authorship and ownership of AI-generated works. It critically examines the limitations of traditional copyright frameworks in addressing the absence of human creators and highlights legal inconsistencies across jurisdictions. By analyzing global perspectives, including examples from the USA, EU, and emerging markets, the article provides a comparative lens on the issue. It also discusses the ethical, economic, and practical implications of protecting AI-generated content, proposing potential legal reforms to foster innovation while ensuring fair attribution. This work serves as a valuable resource for legal scholars, policymakers, and industry stakeholders interested in the evolving role of AI in creative processes.